2019
DOI: 10.1002/hbm.24876
|View full text |Cite
|
Sign up to set email alerts
|

Brain oscillatory activity as a biomarker of motor recovery in chronic stroke

Abstract: In the present work, we investigated the relationship of oscillatory sensorimotor brain activity to motor recovery. The neurophysiological data of 30 chronic stroke patients with severe upper‐limb paralysis are the basis of the observational study presented here. These patients underwent an intervention including movement training based on combined brain–machine interfaces and physiotherapy of several weeks recorded in a double‐blinded randomized clinical trial. We analyzed the alpha oscillations over the moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 57 publications
(101 reference statements)
5
42
0
Order By: Relevance
“…Understanding how NMES parameters, such as intensity and dose, can modulate the excitability of cortical oscillations measured by EEG could be clinically relevant. For instance, NMES could be used for regulating rolandic alpha, since motor recovery has been related to an enhancement of this activity ( Tangwiriyasakul et al, 2014 ; Ray et al, 2020 ), or could be integrated in rehabilitative neural interfaces that are controlled by sensorimotor oscillations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how NMES parameters, such as intensity and dose, can modulate the excitability of cortical oscillations measured by EEG could be clinically relevant. For instance, NMES could be used for regulating rolandic alpha, since motor recovery has been related to an enhancement of this activity ( Tangwiriyasakul et al, 2014 ; Ray et al, 2020 ), or could be integrated in rehabilitative neural interfaces that are controlled by sensorimotor oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…The sensorimotor oscillations that mainly comprise the rolandic alpha [(7–13) Hz] and beta [(14–30) Hz] rhythms have been thoroughly used to study cortical involvement during sensorimotor tasks ( Ramos-Murguialday and Birbaumer, 2015 ; López-Larraz et al, 2018 ), being quantified as the event-related (de)synchronization (ERD/ERS) ( Pfurtscheller and Lopes da Silva, 1999 ). Furthermore, it has also been used as a feature for neuromodulation of sensorimotor neural network via proprioception and haptics ( Ray et al, 2020 ; Sebastián-Romagosa et al, 2020 ). To date, only a few studies have reported how oscillatory activity measured with EEG is modulated by NMES ( Vidaurre et al, 2016 , 2019 ; Tu-Chan et al, 2017 ; Corbet et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…After stroke, alpha oscillations in human patients are lower in frequency and more synchronised (Petrovic et al, 2017), while desynchronisation of this activity during recovery is associated with improved motor outcome (Westlake et al, 2012;Ray et al, 2020). Alpha oscillatory power has also been shown to be increased in both the unaffected and affected hemispheres in mice 9 days after stroke when compared to controls (Vallone et al, 2016).…”
Section: Oscillatory Changes After Strokementioning
confidence: 99%
“…A Stroke Recovery Biomarker (SRB) can be defined as an indicator of disease state that can be used as a measure of underlying molecular or cellular processes that may be difficult to measure directly in humans, and could be used to understand the outcome, or predict the recovery or treatment response [5]. Thus, when dealing with a condition as heterogeneous as stroke, validated biomarkers of recovery could help plan treatments and support efficient allocation of resource while maximizing outcome for the patients [7]. Identification of recovery biomarkers shall assist to advance the practice, rehabilitation and recovery after stroke.…”
Section: Introductionmentioning
confidence: 99%